Public Expenditure : Its Defence and Reform - Heald, David (Oxford [Oxfordshire] : M. Robertson, 1983)
The book is intended as a not uncritical defence of the role of public expenditure within an industrialized economy. It defends public expenditure in general, not every individual item of public expenditure in any country at any time.
Includes indexes.
Bibliography: p. 335-362.
osc 16/06/17
Loans
Keywords: Finance, Public; Government Spending Policy